Debate-Based Civic Education and Its Effects on Critical Thinking, Problem-Solving, and Decision-Making in Border Conflict Resolution - Hamidah, Hamidah; Lubis, Maulana Arafat; Amin, Muhammad; Saleh, Yazid (LPPM Universitas Pendidikan Mandalika, 2025)
This study aims to explore and evaluate the effects, contribution levels, and interrelationships of debate-based civic education on students’ critical thinking (CT), problem-solving (PS), and decision-making (DM) skills within the context of border conflict resolution simulations. The study employed a quantitative approach using an experimental method involving 120 participants whose competencies were assessed. Data were collected using open-ended tests and analyzed through inferential statistics, including simple linear regression, t-tests, R-square, and correlation analyses. The findings revealed that debate-based civic education significantly influenced critical thinking (R² = 21.5%), problem-solving (R² = 32.3%), and decision-making (R² = 18.6%). However, the correlations among the independent variables (CT, PS, and DM) were found to be weak. The results emphasize the applied importance of civic education practices in cultivating 21st-century skills among students in higher education institutions.